Impact and Correction of Analytical Positioning on Accuracy of Zircon U-Pb Dating by SIMS - Liu, Yu; Li, Qiu-Li; Ling, Xiao-Xiao; Tang, Guo-Qiang; Li, Jiao; Li, Xian-Hua (Frontiers in Chemistry, 2020)
Secondary ion mass spectrometry (SIMS) is one of the most important analytical tools for geochronology, especially for zircon U-Pb dating. Due to its advantages in spatial resolution and analytical precision, SIMS is the preferred option for multi-spot analyses on single zircon grain with complex structures. However, whether or how much the relative positions of multiple analytical spots on one zircon grain affect the U-Pb age accuracy is an important issue which has been neglected by most researchers. In this study, we carried out a series of investigation on the influence of relative analytical position during zircon U-Pb age analyses, using Cameca IMS 1280-HR instrument. The results demonstrated a significant influence on the second spot, with apparent U-Pb age deviation as high as around 10 % especially on the left and right side with overlap in the raster area. Nevertheless, a linear correlation between a secondary ion centering parameter (DTCA-X) and age deviation in percentage terms was found, and a calibration method was established to correct this position effect. Four zircon standards (91500, M257, TEMORA-2 and Plešovice) were measured to prove the reliability of the established procedure. The original U-Pb apparent data show inconsistent deviation on four directions relative to the datum, while the final U-Pb age results is calibrated to be consistent with their recommended values, within uncertainties of ~1 %. This work calls for re-examination for the previous SIMS U-Pb dating results on core-rim dating strategy, and provides a calibration protocol to correct the relative position effect.